Covert Tracking to Immersive Stimuli in Traumatic Brain Injury Subjects With Disorders of Consciousness - Aklepi, Gabriela; Manolovitz, Brian; Robayo, Linda E; Sarafraz, Amin; Blandino, Carlos Francisco; Arwari, Brian; Sobczak, Evie; Bass, Danielle; Ghamasaee, Pardis; Bolaños Saavedra, Ana; Samano, Daniel; Massad, Nina; et al. (Journal of neurotrauma, 2024)
Eye tracking assessments are clinician dependent and can contribute to misclassification of coma. We investigated responsiveness to videos with and without audio in traumatic brain injury (TBI) subjects using video eye-tracking (VET). We recruited 20 healthy volunteers and 10 unresponsive TBI subjects. Clinicians were surveyed whether the subject was tracking on their bedside assessment. The Coma Recovery Scale-Revised (CRS-R) was also performed. Eye movements in response to three different 30-second videos with and without sound were recorded using VET. The videos consisted of moving characters (a dancer, a person skateboarding, and Spiderman). Tracking on VET was defined as visual fixation on the character and gaze movement in the same direction of the character on two separate occasions. Subjects were classified as "covert tracking" (tracking using VET only), "overt tracking" (VET and clinical exam by clinicians), and "no tracking". A k-nearest-neighbors model was also used to identify tracking computationally. Thalamocortical connectivity and structural integrity were evaluated with EEG and MRI. The ability to obey commands was evaluated at 6- and 12-month follow-up. The average age was 29 (± 17) years old. Three subjects demonstrated "covert tracking" (CRS-R of 6, 8, 7), two "overt tracking" (CRS-R 22, 11), and five subjects "no tracking" (CRS-R 8, 6, 5, 6, 7). Among the 84 tested trials in all subjects, 11 trials (13%) met the criteria for "covert tracking". Using the k-nearest approach, 14 trials (17%) were classified as "covert tracking". Subjects with "tracking" had higher thalamocortical connectivity, and had fewer structures injured in the eye-tracking network than those without tracking. At follow-up, 2 out of 3 "covert" and all "overt" subjects recovered consciousness versus only 2 subjects in the "no tracking" group. Immersive stimuli may serve as important objective tools to differentiate subtle tracking using VET.